Mapping Muslim Behaviors Through Attitudes And Intentions In Choosing Cash Waqf For Economic Independence - Hermuningsih, Sri; Kirana, Kusuma Chandra; Widiastuti, Retno (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2021)
Waqf is an Islamic economic instrument that bases its function on the elements of virtue (birr), kindness (ihsan) and fraternity (ukhuwah). This research aims to analyze the factors of Wakif’s motive in choosing cash waqf in Bantul Regency, Yogyakarta. This study was conducted quantitatively and used Ajzen's Theory of Planned Behavior. Subjective Norms, Government Support, and Self Efficacy on the attitude and intention of the choice to pay cash waqf were the variables in this research. The objects of this study are those who pay the waqf that involves 98 respondents incorporated in Bazwa. The respondents were divided into four districts consist of 35 respondents from Banguntapan, 23 respondents from Bantul City, 11 respondents from Dlingo, and 29 respondents from Kasihan. Data were collected in two types of primary and secondary data. This study used a validity test, reliability test, and path analysis as the data analysis method. The results of this study indicate the factors that influence wakif’s motive in choosing cash waqf are subjective norms, Government Support, and Self Efficacy. Subjective norms had a significant positive effect on the motive through attitude. Self-efficacy is significant for attitude and insignificant for the motive. In contrast, Government support is not significant for attitude and motive, while attitude is significant for the motive